Rancang Bangun Alat Sortir Berdasarkan Warna dan Berat untuk Kapsul Cangkang Keras Menggunakan Metode Finite State Machine - Anes Yales Sakhina (Fakultas Teknik, 2026)
The phenomenon of non-conformity in the uniformity of the weight of capsule compound drugs identified in one of the pharmacies in Indonesia still has a weight non-uniformity of up to 17%, likewise with the research of the phenomenon of non uniformity in the weight of infant paracetamol pulveres up to 27% indicating that it does not comply with the established standards. Sorting tools based on color and weight of capsules are designed to separate weight and color in capsule filling to make it easier to sort a group of capsules so that it is known which capsules are not fully filled or which are filled according to the dose and to separate them according to color groups. The sensors used in this study are micro load cells and TCS3200. Using the finite state machine method, the results of the TCS3200 color sensor on orange and fuchsia red are that the smaller the Euclidean distance, the more accurate it is for orange, the Euclidean value is 8, and for fuschia red the Euclidean value is 8.7, results from the percent error loadcel after linear regression 2.82%.
Reuploud Repository hasyim Juni 2026 Approved by Teddy
Keywords: capsule; finite state machine; sorting